Juridical Analysis of Directors Who Hold Concurrent Positions in Limited Liability Companies - Rahman, Irsan; Polontoh, Herry; Katjong, Rizky Wisudawan; Katjong, Kadir; Katjong, Revie Kurnia (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The practice of concurrent positions carried out by the Board of Directors in the management of a PT does not yet have a legal basis regulated explicitly in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). Concurrent positions lead to legal loopholes that can cause potential losses to the company. This research aims to analyze the practice's suitability with the law's provisions and compare it with policies in the United States. This research uses a normative method with conceptual and statutory approaches and secondary data from relevant regulations. The results show that concurrent positions can cause conflicts of interest, weaken management, and undermine corporate governance. Legislation changes are needed in Indonesia to limit the number of positions a director can hold and impose more severe sanctions for violators. In conclusion, a law revision is needed to strengthen the regulation of concurrent positions to promote better corporate governance.